2013
DOI: 10.1103/physrevb.87.155146
|View full text |Cite
|
Sign up to set email alerts
|

Interface electronic structure in a metal/ferroelectric heterostructure under applied bias

Abstract: The effective barrier height between an electrode and a ferroelectric (FE) depends on both macroscopic electrical properties and microscopic chemical and electronic structure. The behavior of a prototypical electrode/FE/electrode structure, Pt/BaTiO 3 /Nb-doped SrTiO 3 , under in-situ bias voltage is investigated using xray photoelectron spectroscopy. The full band alignment is measured and is supported by transport measurements. Barrier heights depend on interface chemistry and on the FE polarization. A diffe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
27
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 43 publications
7
27
1
Order By: Relevance
“…For the switching pulse P − to P + , the Pt/BTO/NSTO stack resistance R, is higher, consistent with the lower current through the capacitor measured in Ref. 17. The high to low current behavior when switching from P − to P + is due to the increase of the electron barrier height at the bottom interface (BTO/NSTO) of the capacitor (see Figure 7 of Ref.…”
Section: B Simulationssupporting
confidence: 84%
See 3 more Smart Citations
“…For the switching pulse P − to P + , the Pt/BTO/NSTO stack resistance R, is higher, consistent with the lower current through the capacitor measured in Ref. 17. The high to low current behavior when switching from P − to P + is due to the increase of the electron barrier height at the bottom interface (BTO/NSTO) of the capacitor (see Figure 7 of Ref.…”
Section: B Simulationssupporting
confidence: 84%
“…The growth conditions and heterostructure properties are described in Ref. 17. 300 × 300 µm 2 thick Pt electrodes were patterned by ionic beam etching.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent papers have shown that interface properties highly depend on the lattice matching 65 or interface chemistry. 66 At Mg/MgH 2 interfaces, the Mg-H bonding is the most important bonding that leads to interface stability.…”
Section: The Search Of Relative Position Of Two Phasesmentioning
confidence: 99%